Acute oral toxicity of Celtis iguanaea (Jacq.) Sargent leaf extract (Ulmaceae) in rats and mice - GONÇALVES,N.Z. (2015)
RESUMO Celtis iguanaea (Jacq.) Sargent is popularly used to treat urinary infections, kidneys, breast, body aches, rheumatism, asthma, cramps, poor digestion and as a diuretic medicine. This study aims to determine the acute toxicity of the aqueous leaf extract of Celtis iguanaea (Jacq.) Sargent in rodents. After the collection processes, identification, drying and grinding, the lyophilized powder of the leaves produced, by infusion, the aqueous extract and it was dissolved in saline 0.9%. The administration was made by gavage at a dose of 2000 mg kg-1to rats and mice of both genders. The oral toxicity was determined according to the OECD 423 guide. Signs of toxicity were observed for 15 days and classified from 0 to 4 respectively as missing, rare, mild, moderate and severe. The weight of the animals and the physiological parameters such as food intake and excrements production were observed. All animal tissue samples were collected for histological analysis. The extract was included in Type 5 (substance with LD50 higher than 2000 mg kg-1 and less than 5000 mg kg-1), being considered of low toxicity, but the histopathologycal findings suggested nephrotoxicity and cardiotoxicity. The absolute weight of the kidneys and the heart of the male rats and mice increased, but there was no significant raise in the relative weight of the animals’ organs.